ONCE AGAIN ABOUT ANTIFEBRILES - V.К. Tatochenko ("Paediatrician" Publishers LLC, 2007)
The article deals with urgent questions of the rational application of antifebriles among children. The author provides modern data on the efficiency and safety of antifebriles applied in pediatric practices.Key words: fever, antifebriles, paracetamol, ibuprofen, children.